Desulfovibrio desulfuricans and its derived metabolites confer resistance to FOLFOX through METTL3Research in context - Guifang Li; Huan Liu; Yangmeng Yu; Qian Wang; Chen Yang; Yang Yan; Fang Wang; Yong Mao (EBioMedicine, 2024)
Summary: Background: Chemoresistance is a critical factor contributing to poor prognosis in clinical patients with cancer undergoing postoperative adjuvant chemotherapy. The role of gut microbiota in mediating resistance to tumour chemotherapy remains to be investigated. Methods: Patients with CRC were categorised into clinical benefit responders (CBR) and no clinical benefit responders (NCB) based on chemotherapy efficacy. Differential bacterial analysis using 16S rRNA sequencing revealed Desulfovibrio as a distinct microbe between the two groups. Employing a syngeneic transplantation model, we assessed the effect of Desulfovibrio on chemotherapy by measuring tumour burden, weight, and Ki-67 expression. We further explored the mechanisms underlying the compromised chemotherapeutic efficacy of Desulfovibrio using metabolomics, western blotting, colony formation, and cell apoptosis assays. Findings: In comparison, Desulfovibrio was more abundant in the NCB group. In vivo experiments revealed that Desulfovibrio colonisation in the gut weakened the efficacy of FOLFOX. Treatment with Desulfovibrio desulfuricans elevates serum S-adenosylmethionine (SAM) levels. Interestingly, SAM reduced the sensitivity of CRC cells to FOLFOX, thereby promoting the growth of CRC tumours. These experiments suggest that SAM promotes the growth and metastasis of CRC by driving the expression of methyltransferase-like 3 (METTL3). Interpretation: A high abundance of Desulfovibrio in the intestines indicates poor therapeutic outcomes for postoperative neoadjuvant FOLFOX chemotherapy in CRC. Desulfovibrio drives the manifestation of METTL3 in CRC, promoting resistance to FOLFOX chemotherapy by increasing the concentration of SAM. Funding: This study is supported by Wuxi City Social Development Science and Technology Demonstration Project (N20201005).